Molecular Etiology of Hereditary Single-Side Deafness: Its Association With Pigmentary Disorders and Waardenburg Syndrome - Kim, Shin Hye (Wolters Kluwer Health, 2015)
Unilateral sensorineural hearing loss (USNHL)/single-side deafness (SSD) is a frequently encountered disability in children. The etiology of a substantial portion of USNHL/SSD still remains unknown, and genetic causes have not been clearly elucidated. In this study, the authors evaluated the heritability of USNHL/SSD.